2021
DOI: 10.3390/jcm10112274
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Clinical Course of COVID-19 Patients Treated at a German Tertiary Center during the First and Second Waves in the Year 2020

Abstract: In this study, we directly compared coronavirus disease 2019 (COVID-19) patients hospitalized during the first (27 February–28 July 2020) and second (29 July–31 December 2020) wave of the pandemic at a large tertiary center in northern Germany. Patients who presented during the first (n = 174) and second (n = 331) wave did not differ in age (median [IQR], 59 years [46, 71] vs. 58 years [42, 73]; p = 0.82) or age-adjusted Charlson Comorbidity Index (median [IQR], 2 [1, 4] vs. 2 [0, 4]; p = 0.50). During the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
1
12
0
5
Order By: Relevance
“…A similar observation was made in a large study of patients with hematological malignancies on behalf of the European Hematology Association (EHA), with a significantly decreased mortality rate between the first (March–May 2020) and the second COVID-19 wave (October–December 2020, 40.7 % vs. 24.8 %) 16 . In contrast, several studies on hospitalized COVID-19 patients show diverging results with both equal, lower and increased in-hospital mortality in the later phases of the pandemic 38 , 39 , 40 . Comparing treatment modalities is hindered by the variety of treatments used, but only 6.1 % of patients in our cohort received specific monoclonal antibodies that were not available in the first phases.…”
Section: Discussionmentioning
confidence: 89%
“…A similar observation was made in a large study of patients with hematological malignancies on behalf of the European Hematology Association (EHA), with a significantly decreased mortality rate between the first (March–May 2020) and the second COVID-19 wave (October–December 2020, 40.7 % vs. 24.8 %) 16 . In contrast, several studies on hospitalized COVID-19 patients show diverging results with both equal, lower and increased in-hospital mortality in the later phases of the pandemic 38 , 39 , 40 . Comparing treatment modalities is hindered by the variety of treatments used, but only 6.1 % of patients in our cohort received specific monoclonal antibodies that were not available in the first phases.…”
Section: Discussionmentioning
confidence: 89%
“…In some countries the patients in the second wave were younger than in the first wave, 11 , 12 while other countries did not disclose important differences. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Although some studies have reported a higher occurrence of comorbidities in the first wave, 16 recent studies have not reported differences in the prevalence of comorbidities between the two waves. 12 , 13 It is important to note that vaccination in Brazil started in January 2021, with the elderly and patients with comorbidities as a priority, which is probably one of the factors that would explain the change in the age group observed in the second wave and, consequently, a lower prevalence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the variant alpha (20I/501Y.V1) became rapidly prevalent across Europe in early 2021 [5][6][7] and is now the dominant strain in France, accounting for over 90% of current infections in the Southeastern region of the country [8]. While the clinical presentation of the old strain has been widely described [1][2][3]9], little is known of the clinical characteristics and outcomes of patients infected by the variant alpha. While Challen et al found higher risks of mortality, Frampton et al confirmed the increased transmissibility but not the severity [10,11].…”
Section: Introductionmentioning
confidence: 99%